Trace Detection Method for Tetramine in Drinking Water by Atmospheric Pressure Gas Chromatography-Mass Spectrometry - Duan, Hejun; Feng, Yixing; Niu, Yumin (Asian Journal of Chemistry, 2023)
This study reports a trace detection method for tetramine in drinking water using atmospheric pressure gas chromatography-tandem mass spectrometry (APGC-MS/MS). After dilution with acetone, the drinking water samples were directly measured using APGC-MS/MS. Separation of tetramine was achieved using a DB-5MS weak polar column (30 m × 0.25 mm, 0.25 μm) and detected with APGC ionization source in positive ion mode. Cone gas and auxiliary flow rates were optimized to 250 L/h and 350 L/h, respectively. Quantitative and qualitative analysis was conducted by monitoring two molecular ions of the target compound (m/z 121.6 and m/z 92.6) under multiple reaction monitoring mode (MRM). The linear relationship between tetramine and its concentration was good in the range of 5-100 ng/L, with a correlation coefficient of 0.9999. The detection limit of the method was 0.3 ng/mL and the quantification limit was 1.0 ng/mL. The recovery of the samples was approximately 80.63% to 86.84%, with an intra-day RSD of 1.2% to 3.5% and an inter-day RSD of 2.9% to 4.9%, which met the requirements for trace detection. This method is simple, fast and highly sensitive and it is suitable for the trace detection of tetramine in drinking water.